2016
DOI: 10.1016/j.jvs.2016.04.065
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter 12-month experience with a new iliac side-branched device for revascularization of hypogastric arteries

Abstract: This first ever 1-year study reports the results with the new E-liac device and shows that it can be safely applied for the treatment of aortoiliac aneurysmatic disease with low reintervention rates and high patency rates. Long-term data are needed to confirm the durability of the device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…18,3335 Although Asian patients were found to have a shorter non-aneurysmal CIA compared to the literature when the CIA becomes aneurysmal it also lengthens. When comparing the aorto-iliac length we found that Japanese patients had similar lengths (181.6 ± 27.5 mm) compared to patients treated in America (183.6 ± 28.3 mm) which is somewhat surprising given Japanese patients are noted to be of a shorter average height.…”
Section: Discussionmentioning
confidence: 81%
“…18,3335 Although Asian patients were found to have a shorter non-aneurysmal CIA compared to the literature when the CIA becomes aneurysmal it also lengthens. When comparing the aorto-iliac length we found that Japanese patients had similar lengths (181.6 ± 27.5 mm) compared to patients treated in America (183.6 ± 28.3 mm) which is somewhat surprising given Japanese patients are noted to be of a shorter average height.…”
Section: Discussionmentioning
confidence: 81%
“…20 Moreover, hypogastric branch devices occlude frequently, both early and at midterm. 21,22 In the absence of clear recommendations, clinical judgement should consider the risk of endoleak by sub-optimal seal at the common iliac artery and balance this with the increased risk of occlusion when extending to the external iliac artery.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomic prerequisites of both devices were described. 11,16 The indication for treatment in this cohort was the presence of a unilateral or bilateral CIA ≥35 mm in diameter or an aneurysmal CIA ≥20 mm in diameter associated with an AAA ≥55 mm in diameter. When the abdominal aortic diameter was ≥35 mm or in the absence of a suitable proximal CIA neck, the IBD implantation was associated with a bifurcated EVAR stent-graft.…”
Section: Parameters For Ibd Usementioning
confidence: 99%
“…Several studies evaluating the feasibility and short-and midterm results of commercially available IBDs have documented excellent performance of these devices. [8][9][10][11][12] Nevertheless, only a few studies have directly compared the performance of 2 IBDs, [13][14][15] namely, the Zenith Branch Endovascular Graft-Iliac Bifurcation (ZBIS; Cook Medical Inc, Bloomington, IN, USA) and the Gore Excluder Iliac Branch Endoprosthesis (IBE; W.L. Gore & Associates Inc, Flagstaff, AZ, USA).…”
Section: Introductionmentioning
confidence: 99%